BEHAVIORAL PREVENTION OF HEPATITIS A IN PANDAN JAYA HEALTH CENTER AREA, TANJUNG JABUNG TIMUR REGENCY, JAMBI - Rumita Ena Sari; Rinaldi Daswito (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2018)
Hepatitis A outbreaks were recorded in 2012 and 2014 in Geragai Subdistrict, Tanjung Jabung TimurRegency, Jambi.The highest outbreak occurred in 2014. The purpose of this study was to analyze thebehavior of prevention of Hepatitis A disease including knowledge, attitude, immunization, sharing ofdrinking and eating equipment, eating and drinking practice together, and hand washing with soap atPandan Jaya Health Center Tanjung Jabung Timur Regency. Crossectional study design was performedwith a sample size of 103 respondents, sample was taken by simple random sampling. A total of 53people with Hepatitis A positive in 2016 was observed in this study. There was 61.2% of respondentshad a good knowledge about Hepatitis A, 58.3% of respondents had a positive attitude, 44.7% ofrespondents got Hepatitis A immunization. A total of 45.6% of respondents use cutlery and drinkingtogether, 41.7% of respondents consume food and beverages together and 35% of respondents washedhands with soap. There was a correlation between hand washing with soap with the incidence ofHepatitis A (Pvalue = 0,022, and OR = 0,386), while knowledge, attitude, immunization, sharing anddrinking practices, eating and drinking practice together were not associated with the cases of HepatitisA. Hand washing with soap was a variable having a significant relationship to the incidence ofHepatitis A disease. Pandan Jaya Health Center should make efforts to increase the public knowledgeabout the dangers of Hepatitis A, practice of clean and healthy life behavior, particulary to promote theculture of hand washing with soap. Keywords: Infectious disease, hepatitis A, healthy behaviour, hand wash